Pemahaman Konsep Dinamika dan Kinematika Berdasarkan Conceptual Knowledge Melalui Aplikasi Game Quizizz - Rikardus Feribertus Nikat*; Algiranto Algiranto; Martha Loupatty; Anderias Henukh (Jurnal Pendidikan Sains Indonesia, 2022)
Understanding the concept of physics is the basic cognitive skill to understand, know, apply and analyze a physical phenomenon.  Problems of conceptual knowledge of physics Students are minimal causing their inability to solve problems with Physics. The understanding of physical concepts can be learned in several ways, one of which is based on conceptual knowledge. Conceptual knowledge can be classified based on several sub dimensions of knowledge including knowledge of classifying, generalizing, basic or general concepts. The purpose of this research is to analyze and describe the understanding of physical concepts based on several indicators of conceptual knowledge through the Quizizz Online Game application. This research uses quantitative-qualitative mixed research methods that are interpreted together. Data retrieval techniques use test instruments and in-person interviews. The results showed that the average understanding of student concepts is in a moderate category with a concept understanding index reaching 47%. Students' concept understanding on each conceptual knowledge such as classifying, generalizing knowledge and knowledge of concepts or theories with results at a moderate level